2013
DOI: 10.3349/ymj.2013.54.2.516
|View full text |Cite
|
Sign up to set email alerts
|

Relation among the Gross Motor Function, Manual Performance and Upper Limb Functional Measures in Children with Spastic Cerebral Palsy

Abstract: PurposeThe objective of this study was to describe hand function in relation with gross motor function and subtype of spastic cerebral palsy and to investigate the relationships among gross motor function, bimanual performance, unimanual capacity and upper limb functional measures in children with spastic cerebral palsy (CP).Materials and MethodsWe collected upper extremity data of 140 children with spastic CP. The Gross Motor Functional Classification System (GMFCS) was used to assess gross motor function, Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…Compagnone et al also found a significant statistical association between the Manual Ability Classification System and the Gross Motor Function Classification System specifically limited to the lowest level of function (level V) ( 18 ). Similar conclusions were partially reached by Park et al with reference to the relation between the Gross Motor Function Classification System and the Manual Ability Classification System ( 39 ). In this study, it is shown that the lower levels of the Gross Motor Function Classification System the children were at, the lower levels of the Mini-MACS they were classified ( Figure 2 ), which suggested that Mini-MACS is also correlated to the Gross Motor Function Classification System.…”
Section: Discussionsupporting
confidence: 78%
“…Compagnone et al also found a significant statistical association between the Manual Ability Classification System and the Gross Motor Function Classification System specifically limited to the lowest level of function (level V) ( 18 ). Similar conclusions were partially reached by Park et al with reference to the relation between the Gross Motor Function Classification System and the Manual Ability Classification System ( 39 ). In this study, it is shown that the lower levels of the Gross Motor Function Classification System the children were at, the lower levels of the Mini-MACS they were classified ( Figure 2 ), which suggested that Mini-MACS is also correlated to the Gross Motor Function Classification System.…”
Section: Discussionsupporting
confidence: 78%
“…Active wrist extension is moderately to highly related to manual abilities [43,64]. In the current study, 12 of 17 participants increased active wrist extension by at least 5 degrees.…”
Section: Body Functionmentioning
confidence: 42%
“…Understanding the interrelationships between hand skills and how these are related to MA in children with CP is crucial for planning and implementing the most appropriate rehabilitation interventions. According to previous studies in children and adolescents with CP, MA was not related to passive range of motion ( 15 ), but was moderately to highly related to other hand motor skills (e.g., active range of motion, muscle tone/strength/coordination, dexterity, and quality of movement) ( 3 , 15 20 ). Touch-pressure detection and proprioception were weakly or not associated with MA, whereas two-point discrimination and stereognosis were moderately to highly related to MA ( 3 , 15 ).…”
Section: Introductionmentioning
confidence: 87%